Diverse functionality among human NK cell receptors for the C1 epitope of HLA-C: KIR2DS2, KIR2DL2, and KIR2DL3 - Moesta, Achim K.; Parham, Peter (Frontiers in Immunology, 2012)
Interactions between killer immunoglobulin-like receptors (KIRs) and their HLA-A, -B, and –C ligands diversify the functions of human natural killer cells. Consequently, combinations of KIR and HLA genotypes affect resistance to infection and autoimmunity, success of reproduction and outcome of hematopoietic cell transplantation. HLA-C, with its C1 and C2 epitopes, evolved in hominids to be specialized KIR ligands. The system’s foundation was the C1 epitope, with C2 a later addition, by several million years. The human inhibitory receptor for C1 is encoded by KIR2DL2/3, a gene having two divergent allelic lineages: KIR2DL2 a B KIR haplotype component and KIR2DL3 an A KIR haplotype component. Although KIR2DL2 and KIR2DL3 exhibit quantitative differences in specificity and avidity for HLA-C, they qualitatively differ in their genetics, functional effect and clinical influence. This is due to linkage disequilibrium between KIR2DL2 and KIR2DS2, a closely related activating receptor that was selected for lost recognition of HLA-C.